2020
DOI: 10.1016/j.tim.2019.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Host–Virus Interactions: Implications for Viral Host Range and Virulence

Abstract: A growing number of studies indicate that host-species-specific and virus-strain-specific interactions of viral molecules with the host innate immune system play a pivotal role in determining virus host range and virulence. Because interacting proteins are likely constrained in their evolution, mutations that are selected for to improve virus replication in one species, may stochastically alter the ability of a viral antagonist to inhibit immune responses in hosts the virus has not yet encountered. Based on re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 89 publications
2
77
0
Order By: Relevance
“…VACV K3 has well-defined species-specific differences in its ability to inhibit PKR across the mammalian phylogeny, defined by both LBR assays and yeast-based studies [8,9,17]. The data presented here support and extend this species-specific sensitivity of PKR to VACV K3L and add to a growing body of evidence that virus-specific differences play an important role in viral host range, as do species-specific differences in host genes [22,23]. Consistent with this concept, in this study we showed that the VACV K3 orthologs from four different orthopoxviruses display dramatic differences in their ability to inhibit PKR from different species, including different sensitivities in closely related species such as mice and rats.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…VACV K3 has well-defined species-specific differences in its ability to inhibit PKR across the mammalian phylogeny, defined by both LBR assays and yeast-based studies [8,9,17]. The data presented here support and extend this species-specific sensitivity of PKR to VACV K3L and add to a growing body of evidence that virus-specific differences play an important role in viral host range, as do species-specific differences in host genes [22,23]. Consistent with this concept, in this study we showed that the VACV K3 orthologs from four different orthopoxviruses display dramatic differences in their ability to inhibit PKR from different species, including different sensitivities in closely related species such as mice and rats.…”
Section: Discussionsupporting
confidence: 63%
“…In line with this is a recent report that shows that VACV strains that contain different poxvirus K3 orthologs as their only PKR inhibitors exhibited different replication profiles in cell lines from different species, with some strains showing broader host ranges, whereas others showed narrower host ranges [29]. In a broader context, these chance susceptibilities of host antiviral factors to viral inhibitors that a host has otherwise never been exposed to might play an important role in cross-species transmission of viruses [23].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…However, the manner in which key immune cell subsets change and their states during COVID-19 have remained largely unclear. Thus, defining these key cellular subsets and their states in COVID-19 is a crucial step in obtaining critical insights into the immune clearance mechanism and developing new therapeutic strategies for COVID- 19.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of evidence suggested that hostand virus-specific interactions of viral molecules with the host innate immune system are determinants of virus-host range and virulence (Rothenburg and Brennan 2019). Thus, different species-specific cell types would be necessary in cases of narrow host range such as Nectin4 that is naturally expressed on bovine cells and does not interact with viruses recognizing murine Nectin4, and that variola virus causes solely human smallpox (Haller et al 2014).…”
Section: Technical Obstacles Impose Challenges For Constructing Cellsmentioning
confidence: 99%